Classifying Software Requirements Using Kano's Model to Optimize Customer Satisfaction - Balsam, A. Mustafa (IOS Press, 2014)
Requirements elicitation is a critical and error-prone stage in software development where user requirements should be defined accurately to ensure the success of the software system. In a highly competitive market, businesses are focusing more on satisfying customer needs which largely affect customers decision to buy the software product, providing the potential for the success of the software in the market. This study aims to investigate whether eliciting and thus fulfilling most of the individual software requirements imply a high level of customer satisfaction and what type of requirements that define the perceived product quality and as a result customer satisfaction.